APLIKASI MOVING BED BIOFILM REACTOR (MBBR) DENGAN MEDIA BAMBU UNTUK MENGURANGI KADAR PENCEMARAN AIR SUNGAI (STUDI KASUS ANAK SUNGAI MUDING KAJA) - Dwiyana, Dewa Arya; Suarna, I Wayan; Sila Dharma, I Gusti Bagus (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 16 No 2 (2022)DO - 10.24843/EJES.2022.v16.i02.p06, 2022)
Changes in the function of land on the riverbanks into residential areas have triggered a large amount of organic material that enters into river water, causing river water to degradation in quality. If we ignored this, it will trigger the growth of pathogenic bacteria that endanger human life. One alternative way to overcome the degradation in river water quality due to increased organic material is using the MBBR method with bamboo as its media. This one of method that uses the growth of bacteria attached to the media to reduce the organic material content in river water. The purpose of this experiment was to determine the effect piece of bamboo media and the biggest effectiveness value of reducing BOD and COD levels in Muding Kaja tributary water with a determined of filling ratio, dissolved oxygen and detention time. The results show that the highest effectiveness using the MBBR method with bamboo media can reduce BOD level until 90,946 % with filling ratio 30% and time detention as long 5 hours and reduce COD level until 30,435 % by using filling ratio 30% and time detention for 5 hours. From this research we can conclude that MBBR method using bamboo as media affected to reduce BOD 5 dan COD level. MBBR Method  very efffective to reduce BOD 5 level and less effective to reduce COD level in water river. Keywords: River water pollution, Moving Bed Biofilm Reactor, Bamboo media, Effectiveness